2007
DOI: 10.1042/bj20070479
|View full text |Cite
|
Sign up to set email alerts
|

Mutant α-galactosidase A enzymes identified in Fabry disease patients with residual enzyme activity: biochemical characterization and restoration of normal intracellular processing by 1-deoxygalactonojirimycin

Abstract: Fabry disease is a lysosomal storage disorder caused by the deficiency of alpha-Gal A (alpha-galactosidase A) activity. In order to understand the molecular mechanism underlying alpha-Gal A deficiency in Fabry disease patients with residual enzyme activity, enzymes with different missense mutations were purified from transfected COS-7 cells and the biochemical properties were characterized. The mutant enzymes detected in variant patients (A20P, E66Q, M72V, I91T, R112H, F113L, N215S, Q279E, M296I, M296V and R30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
134
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 47 publications
6
134
0
3
Order By: Relevance
“…9,11,17,20 However, the clinical manifestations of patients with p.E66Q in the cited reports were not sufficiently convincing to confirm p.E66Q as a disease-causing mutation. For instance, Nakao et al 11 suggested that renal variants have a phenotype intermediate between cardiac variants and classical phenotypes.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…9,11,17,20 However, the clinical manifestations of patients with p.E66Q in the cited reports were not sufficiently convincing to confirm p.E66Q as a disease-causing mutation. For instance, Nakao et al 11 suggested that renal variants have a phenotype intermediate between cardiac variants and classical phenotypes.…”
Section: Discussionmentioning
confidence: 80%
“…8,17,19,20 Indeed, we have reported p.E66Q activities as high as 40% of mean normal activity in the transiently overexpressed COS-7 cells. 19 X-ray crystallography shows that GLA is a homodimeric glycoprotein in which each monomer is composed of two domains (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations